Can eight weeks of judo and taekwondo physical education improve the health-related fitness of male university students? - Mohammed H.H. Mohammed; Hong J. Choi (Physical Education of Students, 2020)
Background and Study Aim: This study aimed to determine if Judo and Taekwondo in a physical education (PE) setting could improve the fitness of university students.